SMART TECHNOLOGIES TRANSFORMING EDUCATION, HEALTHCARE, BUSINESS AND SOCIAL DEVELOPMENT SYSTEMS - Pradeep Singh; Anusha Vidyasagar; Pooja Mailsamy; Shanti Jaiswal; Shams Tabrej; Anshu Malhotra (International Journal of Computer Information Systems and Industrial Management Applications, 2026)
Smart technologies increasingly reshape institutional processes, yet evidence remains fragmented across education, healthcare, business, and social development. This paper develops and evaluates a unified cross-sector transformation model linking smart technology capability, process integration, governance readiness, and digital inclusion to system-level outcomes. Because no field dataset was available, the study uses an explicitly labelled Monte Carlo simulation of 1,200 organizational units, equally allocated across four sectors. Twenty indicators form five composite constructs, and analysis combines reliability assessment, robust regression, bootstrapped mediation, moderation, analysis of variance, and sector-specific estimation. results show that smart technology capability predicts process integration and transformation outcomes; process integration carries a substantial indirect effect; governance readiness strengthens the capability-outcome relationship; and digital inclusion contributes independently. Business units display the highest mean capability and transformation outcome, whereas social development units show the strongest inclusion profile but weaker integration. Cross-sector differences are statistically detectable but modest, indicating shared mechanisms alongside contextual variation. The paper contributes an integrated, governance-sensitive explanation of transformation rather than treating technology adoption as sufficient. Findings are illustrative, not empirical claims about real organizations. They provide transparent propositions, reproducible benchmarks, and policy-oriented priorities for future comparative empirical field validation across sectors and resource settings.